Qualification of W heavy alloys as plasma facing material - B. Böswirth; H. Greuner; S. Elgeti; T. Höschen; K. Hunger; H. Maier; R. Neu (Nuclear Materials and Energy, 2024)
Highly loaded divertor regions in fusion experiments are exposed to high particle and power fluxes. Therefore, tungsten with its excellent thermal and physical properties is a preferred plasma facing material for this application. For divertor areas with moderate steady-state heat flux up to 10 MW/m2 the excellent high-temperature resistance of W is not absolutely necessary. 95–97 % W heavy alloys containing Ni, Cu or Fe could be used from the aspects of plasma wall interaction and their thermomechanical properties. In this study we present results of thermo-mechanical characterisations like measurement of thermal conductivity and tensile tests at elevated temperatures as well as results of high heat flux performance tests at adiabatic and steady-state loading. Finally, we discuss results of deuterium retention measurements.